WASATIYYAH AS FOUNDATION COURSE AT UNIVERSITAS ISLAM INTERNATIONAL INDONESIA - Siregar, Nurhalimah; Aziz, Muhammad Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
The Islamic concept of wasatiyyah is reflected in the Qur’an, which refers to the Muslim community as a moderate people (ummatan wasatan). It means that a Muslim should be in the middle path in many aspects of life, which promotes benefits and avoids extremism. In doing so, education plays a significant role in promoting the concept of wasatiyyah. However, the concept itself has been neglected in the teaching and learning of Islamic higher education, which is an inseparable part of urban Muslim communities. This study is aimed to explore the implementation of the wasatiyyah course at Universitas Islam International Indonesia. The study was conducted qualitatively with a case study research design to investigate students’ perspectives on the wasatiyyah course. A total of four participants with different backgrounds of study, cultures, and religions participated in this study. The data was collected through semi-structured interviews and analyzed with the Miles and Huberman framework. Overall, the result of the study shows that the students perceive positively towards the course of wasatiyyah Islam. In addition, the study also demonstrates students’ reflection on the practice of the concept of wasatiyyah in a plural context. Hence, it recommends reimagining the concept of wasatiyyah in Islamic universities by implementing the idea into the course subjects to promote tolerance and harmony within diversity.